P134 Comparison of Two Prognostic Tools For Identifying High Risk Patients with Idiopathic Pulmonary Fibrosis. (19th November 2012) - Wilkie, MEM; Chalmers, JD; Smith, RP; Schembri, S
Abstract : Introduction: Idiopathic pulmonary fibrosis (IPF) is a progressive disease with median survival of 2–3 years. Clinical course and survival is variable. Whilst no universally accepted tool is accessible to identify those with poorer prognosis, du Bois et al (1) and Ley et al (2) propose individual 4 point scoring systems to calculate mortality. Our aim was to compare both tools and assess for superiority. Methods: Data was collected on 101 patients retrospectively, 13 were excluded. The du Bois score included age, respiratory hospitalisation, baseline forced vital capacity (FVC) and 6 month change in FVC.(1) The GAP index used gender, age, FVC and DLCO.(2) Predictive values were assessed using area under the receiver operator characteristic curve (AUC). We used GAP index >1 and du Bois score >22 to indicate high risk for calculation of performance characteristics. Patients were followed up for 3 years or until death. Results: Median age was 69 years (interquartile range 63–76). 57.5% were male. 1 year mortality was 10.2%, compared with 18.2% at year 3. For prediction of 1 year mortality, the AUC was 0.78 (0.69–0.87) for the du Bois score and 0.73 (0.63–0.84) for the GAP index. For 3 year mortality, the AUC was 0.73 (0.65–0.80) for both systems. There was no significant difference between the scores for either outcome (p=0.5 and p=0.9 respectively). The receiver operator characteristic curves for 1 year mortality are shown: figure 1 . For 1 year mortality, the GAP index had a sensitivity of 87%, specificity 55% compared to 66.7% and 71.1% for the du Bois score. For 3 year mortality, the GAP index had a sensitivity of 86.7%, specificity 58.9% compared to 62.5% and 73.7% for the du Bois score. Conclusions: This study shows that both systems are of equal value at identifying patients with IPF at high risk of mortality. References: du Bois RM et al. Ascertainment of individual risk of mortality for patients with idiopathic pulmonary fibrosis. Am J Respir Crit Care Med 2011; 184:459–466. Ley B et al. A multidimensional index and staging system for idiopathic pulmonary fibrosis. Ann Intern Med. 2012; 156:684–691.